ENVIRONMENTAL DISPUTE RESOLUTION THROUGH NON-LITIGATION CHANNELS - Karisma, M. Alip (Communale Journal, 2025)
Environmental conservation has now been seen as something that must be considered for people in various regions. This then makes damage to the environment an act that is against the law, so that a claim for rights can be submitted. Discussing the resolution of environmental disputes in a non-litigation manner or outside the court and the procedure for resolving environmental disputes through litigation. Based on the analysis, pollution and environmental damage cause losses for certain parties, such as the community. Dispute resolution outside the court can be pursued through mediation, conciliation or arbitration mechanisms. The natural resource management system implemented by the government so far has caused a number of problems, such as increasing conflicts, environmental damage, and high poverty levels, as well as a lack of attention to the values of local wisdom, the social, economic and cultural system of the local community to overcome these problems. but also provide adequate justice and settlement. Although often unaware, this mechanism has a legal basis that has been implemented and has the potential to be further developed in the future.